DESAIN TATA RUANG PERPUSTAKAAN SEKOLAH DENGAN MENGGUNAKAN SKETCHUP MAKE - Orina Fitri, Mega; Oktavia, Putri (UIN Imam Bonjol Padang, 2022)
School libraries in Indonesia, which do not meet minimum national standards in terms of area and division of space, have caused schools need to rearrange their library rooms to make them comfortable for users. One example is in the SMP Negeri 28 Padang library. The purpose of this study is to make a layout design for the library of SMP Negeri 28 Padang by using SketchUp Make, so that it can fulfill Indonesian national standards in terms of dividing the library areas/rooms and make the rooms comfortable for users and librarians. This research is development research, located in SMP Negeri 28 Padang. Primary data sources are observations and interviews, while secondary ones are journal articles, websites, books, and other supporting documents. Data analysis and processing techniques used qualitative and quantitative. The research product was a layout design for library of the SMP Negeri 28 Padang, and already applied there. Then a field survey was conducted by distributing questionnaires to librarians and users to test the feasibility of the design results. Based on the results of the questionnaire, it can be concluded that the design is very adequate and feasible to be applied.